Reputational concerns moderate the relationship between lying and depression - Oguni, Ryuji; Taguchi, Keiya (Frontiers in Developmental Psychology, 2025)
This cross-sectional study examined whether reputational concerns moderated the relationship between lying and depression in adolescence. We conducted an online survey of 1,022 Japanese high school students between the ages of 15 and 18 (474 males and 548 females). Results showed that the relationship between selfish lying and depression was not moderated by either rejection avoidance or praise seeking. In contrast, the relationship between prosocial lying and depression was moderated by both rejection avoidance and praise seeking. Specifically, when rejection avoidance and praise seeking were high and when rejection avoidance was high and praise seeking was low, those with higher tendencies toward prosocial lying exhibited higher levels of depression. When rejection avoidance was low and praise seeking was high, those with higher tendencies toward prosocial lying had lower levels of depression. Our findings indicate that reputational concerns complexly moderate the relationship between lying and depression in adolescence.